Performing Arts Center - ZUHAIRI, RIMA (My University, 2020)
Art is the science of aesthetics. So I wanted my project to be a SOCIAL MONUMENT and a SCULPTURE. 1. The SOCIAL MONUMENT concept were achieved by many ways : I have chosen the site at Rafedia Street - nearby Qusian-, where several cities meet. Moreover, the site characterized by a unique beautiful natural view which achieved: A. Social dimension. B. Emotional dimension.